Force degradation study on aligner plates immersed in various solutions - Shou-Min Chen; Tsui-Hsein Huang; Chun-Te Ho; Chia-Tze Kao (Journal of Dental Sciences, 2023)
Background/purpose: The strength of aligners themselves has a high decay rate and is susceptible to accelerated degradation in the environment. The purpose of this study was to compare three types of invisible aligner films after being immersed in coffee, tea, cola, and red wine for seven days and to evaluate the changes in their strengths. Materials and methods: Three types of invisible aligner plates with a thickness of 0.75 mm, i.e., Duran T (polyethylene terephthalate glycol, PETG), Biolon (polyethylene terephthalate, PET), and Zendura FLX (polyurethane, PU), were soaked in artificial saliva and four drinks (coffee, tea, cola, red wine) for 1, 4, and 7 days. The strength test was performed by using the three-point bending test method. The residual strength ratio for the same type of invisible correction film at the same time was separately recorded. The independent t-test was used to indicate significant differences at P < 0.05. Results: The Biolon invisible correction film soaked in cola, red wine and artificial saliva showed significant differences on the 1st and 4th days (P < 0.05). The Duran T invisible correction film soaked in coffee and artificial saliva showed significant differences on the first day (P < 0.05). The Zendura FLX invisible correction film had a waterproof layer on the surface, and there was no significant difference between soaking in any drink and soaking in saliva (P > 0.05). Conclusion: Invisible correction films with different ingredients soaked in solutions show a strength decay phenomenon, except for those with TPU ingredients.